A century of “anticoccidial drugs”: bibliometric analysis - Kandeel, Mahmoud; Morsy, Mohamed A.; Abd El-Lateef, Hany M.; Marzok, Mohamed; El-Beltagi, Hossam S.; Al Khodair, Khalid M.; Albokhadaim, Ibrahim; Venugopala, Katharigatta N.; Al-Rasheed, Mohammed; Ismail, Mahmoud M. (Frontiers in Veterinary Science, 2023)
Publications are an important measure of scientific and technological progress. The quantitative examination of the number of publications in a certain research topic is known as bibliometrics. Bibliographic studies are widely used to analyse the condition of research, future potential, and current growth patterns in a certain topic. It can serve as a basis for making decisions and implementing strategies to achieve long-term development goals. To our knowledge, no research has been conducted in these domains; so, this work aims to employ bibliometric analysis to provide comprehensive data on publications related to anticoccidial drugs. As a result, the current study uses bibliometric analysis to track the evolution of anticoccidial drugs and its consequences in the academic and public worlds via a survey of relevant scientific and popular publications. The Dimensions database was used to retrieve the bibliographical statistics, which were then cleaned and analyzed. The data was also loaded into the VOS viewer, which generated a network visualization of the authors with the most joint articles. The investigation discovered three stages of publications and citations since the first article on anticoccidial drugs in 1949. The first stage, which ran from 1920 to 1968, was characterized by a scarcity of research articles on anticoccidial drugs. From 1969 to 2000, the second stage was marked by a stable and marginally increased number of articles. The scientific field was characterized by an increasing trend in the number of publications and their citations from 2002 to 2021. The study gave a complete list of the top anticoccidial drugs funding agents, countries, research institutes, most cited publications, and important co-authorship and partnerships. The outcomes of the study will help veterinary practitioners and researchers understand the trends and best sources of knowledge in the field of anticoccidial medications.